Creditor's protection and bank loans: lack of competition hampers bankruptcy reform's effects - Andrade, Rodrigo Augusto Silva de (2015)
This dissertation investigates how credit institutions’ market power limits the effects of creditor protection rules on the interest rate and the spread of bank loans. We use the Brazilian Bankruptcy Reform of June/2005 (BBR) as a legal event affecting the institutional environment of the Brazilian credit market. The law augments creditor protection and aims to improve the access of firms to the credit market and to reduce the cost of borrowing. Either access to credit or the credit cost are also determined by bank industry competition and the market power of suppliers of credit. We derive a simple economic model to study the effect of market power interacting with cost of lending. Using an accounting and operations dataset from July/2004 to December/2007 provided by the Brazilian Central Bank, we estimate that the lack of competition in the bank lending industry hinders the potential reducing effect of the BBR on the interest rate of corporate loans by approximately 30% and on the spread by approximately 23%. We also find no statistical evidence that the BBR affected the concentration level of the Brazilian credit market. We present a brief report on bankruptcy reforms around the world, the changes in the Brazilian legislation and on some recent related articles in our introductory chapter. The second chapter presents the economic model and the testable hypothesis on how the lack of competition in the lending market limits the effects of improved creditor protection. In this chapter, we introduce our empirical strategy using a differences-in-differences model and we estimate the limiting effect of market power on the BBR’s potential to reduce interest rates and on the spread of bank loans. We use the BBR as an exogenous event that affects collateralized corporate loans (treatment group) but that does not affect clean consumer loans (control group) to identify these effects, using different concentration measures. In Chapter 3, we propose a two-stage empirical strategy to handle the H–Statistics proposed by Panzar and Rosse as a measure of market competition. We estimate the limiting effects of the lack of competition in replacing the concentration statistics by the H–Statistics. Chapter 4 presents a structural break test of the concentration index and checks if the BBR affects the dynamic evolution of the concentration index.